Physical capacity, not skeletal maturity, distinguishes competitive levels in male Norwegian U14 soccer players - Grendstad, H.; Nilsen, A.-K.; Brekke Rygh, C.; Hafstad, A.; Kristoffersen, M.; Vereide Iversen, V.; Nybakken, T.; Vestbøstad, M.; Algrøy, E. A.; Sandbakk, Ø.; Gundersen, H. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The main aim of the present study was to compare skeletal maturity level and physical capacities between male Norwegian soccer players playing at elite, sub-elite and non-elite level. Secondary, we aimed to investigate the association between skeletal maturity level and physical capacities. One hundred and two U14 soccer players (12.8-14.5 years old) recruited from four local clubs, and a regional team were tested for bone age and physical capacities. Bone age was estimated with x-ray of their left hand and used to indicate maturation of the skeleton. Players went through a comprehensive test battery to assess their physical capacities. Between-groups analysis revealed no difference in chronological age, skeletal maturity level, leg strength, body weight, or stature. However, elite players were superior to sub-elite and non-elite players on important functional characteristics as intermittent-endurance capacity (running distance: 1664 m ± 367 vs 1197 m ± 338 vs 693 m ± 235) and running speed (fastest 10 m split time: 1.27 seconds ± 0.06 vs 1.33 seconds ± 0.10 vs 1.39 seconds ± 0.11), in addition to maximal oxygen uptake (VO2max), standing long jump, and upper body strength (P < .05 for all comparisons). Medium-to-large correlations were found between skeletal maturity level and peak force (r = 695, P < .01), power (r = 684, P < .01), sprint (r = -.471, P<.001), and jump performance (r = .359, P < .01), but no correlation with upper body strength, VO2max, or intermittent-endurance capacity. These findings imply that skeletal maturity level does not bias the selection of players, although well-developed physical capacity clearly distinguishes competitive levels. The superior physical performance of the highest-ranked players seems related to an appropriate training environment.